'Nationalising' and Transforming the Public Funding of Early Years Education (and care) in England 1996–2017. Issue 2 (3rd April 2019) - West, Anne; Noden, Philip
ABSTRACT: The public funding of early years education and care in England has been transformed. Historically, local councils had the main responsibility for decisions regarding nursery education and child day care, but in 1996 the Conservative government introduced a nursery education voucher scheme. Parents of four-year-olds could exchange the voucher for three terms of part-time 'preschool provision' in a state maintained nursery or primary school, or in a private, voluntary or independent (PVI) provider of child day care; in 1998, the Labour government replaced the voucher with an entitlement to free part-time 'early education'. The entitlement was expanded progressively and in 2017 the Conservative government introduced 30 h per week free 'childcare' for some children, together with an Early Years National Funding Formula. Funding goals and policy have shifted over time, underpinned by the idea of 'a level playing field' between providers in maintained and PVI sectors. However, there is no statutory requirement for PVI settings to employ qualified teachers, militating against a genuine 'level playing field' and the integration of education and care.